Neighbourhoods in Transition Brownfield Regeneration in European Metropolitan Areas - Rey, Emmanuel (The Urban Book Series, 2022)
This open access book is focused on the intersection between urban brownfields and the sustainability transitions of metreopolitan areas, cities and neighbourhoods. It provides both a theoretical and practical approach to the topic, offering a thorough introduction to urban brownfields and regeneration projects as well as an operational monitoring tool. Neighbourhoods in Transition begins with an overview of historic urban development and strategic areas in the hearts of towns to be developed. It then defines several key issues related to the topic, including urban brownfields, regeneration projects, and sustainability issues related to neighbourhood development. The second part of this book is focused on support tools, explaining the challenges faced, the steps involved in a regeneration process, and offering an operational monitoring tool. It applies the unique tool to case studies in three selected neighbourhoods and the outcomes of one case study are also presented and discussed, highlighting its benefits. The audience for this book will be both professional and academic. It will support researchers as an up-to-date reference book on urban brownfield regeneration projects, and also the work of architects, urban designers, urban planners and engineers involved in sustainability transitions of the built environment.